(untitled) (CAHIERS MAGELLANES-NS, 2024)
Ignoring occupational safety at work may lead to health, economic and social disorders. Iraq people are one of the societies that rarely care about occupational safety, especially in the agriculture, industry, transportation, urban and rural sectors. The study aimed to evaluate the application of occupational safety of 300 patients in rural areas who attended public health hospitals around Baghdad (Al-Kadhimia, Al- Alermok, and Al-Mahmoudiya) for the period from 1st of April to 30th of September 2023. The results showed that the majority of patients were women 68% also they were more in contact with biological causes due to frequent touching with animals by milking process, providing feed, cleaning animal house while men were more publicity to physical and chemical injury, such as accidents, toxicity or sensitivity from pesticides. The biological diseases recorded were brucellosis, typhoid, hydatid cysts and other infectious skin diseases such as scabies, or dermatophytosis. So, in Iraq occupational safety application of livestock breeders was very weak, Therefore, the rural person must adhere to occupational safety rules to reduce exposure to various risks, during wearing personal protective equipment such as gloves, long boots and full body suits, also increase awareness of the importance of occupational safety through the media, veterinary and agricultural organizations.